2003
DOI: 10.1016/s0032-9592(03)00035-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of l-glutaminase by an immobilized marine Pseudomonas sp BTMS-51 in a packed bed reactor

Abstract: A marine Pseudomonas sp BTMS-51, immobilized by Ca-alginate gel entrapment was used for the production of extracellular Lglutaminase under repeated batch process and continuous process employing a packed bed reactor (PBR). Immobilized cells could produce an average of 25 U/ml of enzyme over 20 cycles of repeated batch operation and did not show any decline in production upon reuse. The enzyme yield correlated well with the biomass content in the beads. Continuous production of the enzyme in PBR was studied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 15 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…In the case of fungi both intra and extracellular glutaminase from Aspergillus oryzae were inhibited by Hg, Cr and Fe but were not affected by sulphydroxyl reagents. EDTA, Na 2 SO 4 , and p-c Woromercuribenzoate strongly inhibited the Micrococcus luteus glutaminase I while glutaminase II was inhibited by EDTA, HgCh, Na 2 SO 4 , CuCh and FeCh 39 .…”
Section: Effect Of Various Substances and Heavy Metalsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the case of fungi both intra and extracellular glutaminase from Aspergillus oryzae were inhibited by Hg, Cr and Fe but were not affected by sulphydroxyl reagents. EDTA, Na 2 SO 4 , and p-c Woromercuribenzoate strongly inhibited the Micrococcus luteus glutaminase I while glutaminase II was inhibited by EDTA, HgCh, Na 2 SO 4 , CuCh and FeCh 39 .…”
Section: Effect Of Various Substances and Heavy Metalsmentioning
confidence: 91%
“…However, it was reported that addition of glucose enhanced the enzyme production in C. nodaensis 38 , Pseudomonas sp. 39 , Streptomyces rimosus 40 , Providencia sp. 41 , T. koningii 42 and Beauveria sp.…”
Section: Effect Of Additional Carbon and Nitrogen Sources On L-glutammentioning
confidence: 99%
See 1 more Smart Citation
“…A glutaminaseasparaginase enzyme from Achromobacter has shown anti leukemic effects in patients with acute lymphoblastic leukemia and acute myelois leukemia in a preliminary clinical trial [65]. Moreover, one of the most promising therapeutic applications ever proposed for the L-glutaminase is in treatment of HIV [66].…”
Section: Applications Of Microbial Amidases Therapeutic Applicationsmentioning
confidence: 99%
“…In recent years, L-glutaminase has received attention as a therapeutic agent against cancer and HIV (Roberts et al, 1970;Chandrasekaran et al, 1991;Kumar and Chandrasekaran, 2003), as a bio-sensing agent in monitoring glutamine levels (Kashyap et al, 2002;Zhao et al, 2004), for the production of specialty chemicals like theanine by c-glutamyl transfer reactions and as a flavour enhancer in the food industry (Sivakumar et al, 2006). The use of L-glutaminase as a flavour-enhancing agent in Chinese foods has replaced the use of monosodium glutamate which acts as an allergen for individuals (Rohde et al, 1996;Masuoa et al, 2004;Thongsanit et al, 2008;Jeon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%